2005
DOI: 10.2174/0929867054367130
|View full text |Cite
|
Sign up to set email alerts
|

Drug Development and PET-Diagnostics for Alzheimers Disease

Abstract: The exact cause of Alzheimer's disease is still unknown; despite the dramatic progress in understanding. Most gene mutations associated with Alzheimer's disease point to the amyloid precursor protein and amyloid beta. The alpha-, beta- and gamma-secretases are the three executioners of amyloid precursor protein processing. Significant progress has been made in the selective inhibition of these proteases, regardless of the availability of structural information. Several peptidic and non-peptidic leads were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 163 publications
(223 reference statements)
0
19
0
Order By: Relevance
“…[1] The pathological hallmarks of AD are extracellular deposits of aggregated amyloid b (Ab) peptide and intracellular neurofibrillary tangles (NFTs). The major proteinaceous components of NFTs are abnormal filaments, termed either straight filaments (SFs) or paired helical filaments (PHFs).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The pathological hallmarks of AD are extracellular deposits of aggregated amyloid b (Ab) peptide and intracellular neurofibrillary tangles (NFTs). The major proteinaceous components of NFTs are abnormal filaments, termed either straight filaments (SFs) or paired helical filaments (PHFs).…”
Section: Introductionmentioning
confidence: 99%
“…Cleavage at the Ab N-terminus is executed by the b-site cleaving enzyme (BACE). 2,3 The following intramembrane cleavage by c-secretase occurs with little sequence specificity, resulting in Ab fragments of different length, predominantly Ab 40 , Ab 42 and some Ab 38 . Ab 42 being the most aggregatory.…”
mentioning
confidence: 99%
“…The amyloid cascade hypothesis holds that the aggregation and deposition of Aβ peptides as amyloid plaques is the process responsible for the onset of symptomatic AD [99]. Consequently, lowering Aβ levels is the target of many drugs in development for AD, such as β-secretase inhibitors, γ-secretase inhibitors, and antibodies raised against Aβ [5]. It has been demonstrated that amyloid plaques exist in a state of equilibrium with soluble Aβ, and that antibodies enhancing Aβ clearance or drugs inhibiting Aβ production will shift the equilibrium such that amyloid plaques will diminish [100].…”
Section: Amyloid Plaque Imaging Agentsmentioning
confidence: 99%
“…However, there is currently a lack of sensitive and specific biomarkers for early AD [3]. Imaging modalities such as MRI and PET are used more and more frequently for biomarker quantitation [4], and the field of imaging has become increasingly active in the pursuit of an imageable biomarker for AD [5][6][7]. Provided with a validated biomarker, imaging techniques could potentially be used as a non-invasive tool to aid in early diagnosis, assess the efficacy of disease-modifying agents in the development of new drugs, and to monitor treatment of new therapies for AD.…”
Section: Introductionmentioning
confidence: 99%